PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA PADA MATERI KONDUKSI DAN KONVEKSI PANAS - Mihfadh Mihfadh (LPPM UNISDA, 2018)
The purpose of this research is to increase students' activity in learning process and science learning result of Biology of VIIIA grade of junior high school student of Al-Amin Paciran. This classroom action research is conducted in class VIIIA SMP Al-Amin Paciran through 2 learning cycles and each cycle includes 4 stages, namely planning stage, implementation stage, observation stage and reflection stage. From the results of data analysis, it can be seen that the result of student activity observation discussed in cycle 1: 60%, while in the second cycle rose to 75.17%. For the activity of students in role play in cycle 1: 65.50%, while in the second cycle rose to 74% ,. For student learning outcomes in the first cycle of 64.40%), while in the second cycle rose to 95.50%. Thus, it can be concluded that the application of a combination of discussion methods and role playing methods in the learning process can improve the activity and learning outcomes.